2016
DOI: 10.1515/ncrs-2015-0221
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of (η 5-pentamethylcyclopentadienyl)titanium(III)dichloride (THF), C14H23Cl2OTi

Abstract: C14H 23 Cl 2 OTi, monoclinic, P21/c (no. 14), a = 12.3163 (7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 12 publications
5
7
0
Order By: Relevance
“…The κ 2 ‐coordinated BH 4 groups agree with the long Ti⋅⋅⋅B distances of 2.389(4) and 2.402(3) Å when compared with that found (2.220(9) Å) for the κ 3 ‐BH 4 ligands of complex 4 [32] . The Ti−O bond length of 2.111(2) Å compares well with those found in other titanium(III) tetrahydrofuran adducts such as [Ti(η 5 ‐C 5 Me 5 )Cl 2 (thf)] (Ti−O=2.083(2) Å) [11,37] …”
Section: Resultssupporting
confidence: 81%
“…The κ 2 ‐coordinated BH 4 groups agree with the long Ti⋅⋅⋅B distances of 2.389(4) and 2.402(3) Å when compared with that found (2.220(9) Å) for the κ 3 ‐BH 4 ligands of complex 4 [32] . The Ti−O bond length of 2.111(2) Å compares well with those found in other titanium(III) tetrahydrofuran adducts such as [Ti(η 5 ‐C 5 Me 5 )Cl 2 (thf)] (Ti−O=2.083(2) Å) [11,37] …”
Section: Resultssupporting
confidence: 81%
“…6a Indeed, Gambarotta and co-workers have demonstrated that [Ti( 5 -C5H5)Cl2(thf)1.5] crystallizes as an equimolar mixture of the four-and five-coordinate complexes [Ti( 5 -C5H5)Cl2(thf)] and [Ti( 5 -C5H5)Cl2(thf)2]. 36,37 As previously observed in several studies, 11-20 14 the tetrahydrofuran ligand in 4 is only weakly coordinated. Thus, once crystals of 4 are separated from the solution, the tetrahydrofuran is gradually lost within hours at room temperature to give the dinuclear compound 2.…”
Section: Resultsmentioning
confidence: 69%
“…The Ti-Cl bond lengths in 7 and 9 of 2.3331 (3)-2.3804 (4) Å are also in the range of typical Ti-Cl bond lengths, e.g. Cp 2 TiCl 2 [2.367 (2) and 2.361 (1) Å ; Clearfield et al, 1975], Cp*TiCl 2 (thf) [thf is tetrahydrofuran; 2.3426 (2) and 2.3251 (6) Å ; Oswald et al, 2016], TiCl 3 py 3 -(NCy 2 ) [Cy is cyclohexyl; 2.3653 (5), 2.3393 (5) and 2.3023 (5) Å ; Adler et al, 2014] or other complexes (Kessler et al, 2013;Sassmannshausen & Baumgartner, 2008;Edwards et al, 1995); the bond lengths are also in accordance with the already published structure of 8 (Diekmann et al, 2006). As The molecular structure of complex 9.…”
Section: Figurementioning
confidence: 85%